تقييم جودة العملية التدريسية في قسم الجغرافيا بكلية الآداب غريان من وجهة نظر الطلاب (Comprehensive Journal of Science, 2026)
This study aims to evaluate the quality of the teaching process in the Department of Geography at the Faculty of Arts – Gharyan, from the students’ perspective. The study sample consisted of 26 students from the Geography Department, and a questionnaire was used as the data collection tool. The results showed that the quality of teaching planning was high, with a mean score of 2.73 and a percentage of 91%, particularly in clearly stating the course objectives at the beginning of the semester. The quality of teaching implementation was also high, with a mean of 2.84 and a percentage of 94.6%, with the highest rating given to encouraging student participation and interaction, while linking the material to the local context required improvement. Similarly, the quality of assessment methods was high, with a mean of 2.77 and a percentage of 92.3%, though there is a need to clarify evaluation criteria more effectively. Overall, the results reflect students’ satisfaction with the performance of faculty members and the quality of planning, implementation, and assessment practices, while also highlighting opportunities to enhance certain aspects to improve educational effectiveness.